Enterprise management problems in the current crisis situation - Serov, Victor M.; Moiseenko, Natalya A.; Astafyeva, Olga E. (Nexo Revista Científica, 2021)
The paper examines the problems faced by enterprises in the real sector of the economy. These problems are not new; they have been discussed in the scientific community for a decade, but in today's realities, when the entire world economy lives in a pandemic, these problems have become aggravated and require a serious, balanced approach to their solution. All economic crises are primarily reflected in investment activity. That is why it is necessary to highlight economic security to ensure the effectiveness of budget investments. In this area, the bulk of violations and sometimes crimes are observed in the financial and investment area of relations of all participants in business processes in the economy. In general methodological terms, the article substantiates and reveals a proposal for organizing a system of indicative analysis and regulation of production volumes and production and economic activities of enterprises and organizations of the real sector of the economy as an organizational tool for resolving crisis situations in the economy. Both external and internal factors are touched upon, which caused the current unsatisfactory state of the Russian economy. In a concrete plan, the author's proposals on the directions and ways of overcoming the current crisis phenomena in the Russian economy are presented.